Benzopyrano-fused N-heterocyclic polyaromatics - Elbert, Sven; Reinschmidt, Martin; Baumgärtner, Kevin; Rominger, Frank; Mastalerz, Michael (European journal of organic chemistry, 2018)
Polycyclic heteroaromatic compounds are potentially interesting materials for organic electronic applications. While most of those compounds contain nitrogen or sulfur, oxygen-based structures are much rarer, especially those including annulated pyrane rings. By the utilization of a cascade of Pictet-Spengler reactions and thermally induced ipso-substitutions, a series of peri-benzopyrano-fused nitrogen containing polycyclic aromatic compounds was synthesized and their optoelectronic properties investigated by UV/Vis and emission spectroscopy as well as cyclic voltammetry and DFT-calculations.
Gesehen am 18.10.2019